Mauritius : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses how Mauritius is currently dealing with two separate tax transparency and anti-avoidance initiatives, one by the OECD-G20 and one by the European Union. Under the BEPS initiative, Mauritius has committed to including minimum standards and possibly other BEPS-compliant features into its domestic laws and bilateral double taxation avoidance agreements (DTAs). Mauritius has been involved in intensive DTA negotiations and re-negotiations. Sixteen DTAs have been added in the past 6 years. Arguably, even more important for investors has been the favorable tax framework offering benefits that are in part being challenged. Mauritius currently has a 15 percent corporate income tax (CIT) rate and a worldwide system that taxes foreign earnings but allows for foreign tax credits (FTCs), including the contested Deemed Foreign Tax Credit. Important macrofinancial linkages between the GBC sector and the financial sector present vulnerabilities that need to be managed carefully. The GBC sector is a major provider of inexpensive funding to banks, but by nature of the GBC investment pattern, these deposits are potentially highly volatile.